An optimization model-based DEA-MARCOS approach for assessing EU countries towards achieving sustainable development goals - Saha A.; Mishra A.R.; Rani P.; Deveci M.; Debnath B.K.; Jamil N.; Mahmoud M.A. (Elsevier Ltd, 2025)
Sustainable development serves as a guiding principle, striving to achieve human development goals while ensuring that natural systems can support essential ecosystem services and resources. The 2030 Agenda for Sustainable Development, accepted by all United Nations Member States in 2015, offers a unifying framework for peace and prosperity for people and the planet, both now and in the future. The Sustainable Development Goals (SDGs) include specific targets and indicators, helping to assess a country's progress towards achieving the goals. To evaluate the EU (European Union) countries' alignment with the SDGs, this study develops a group decision-making approach by integrating DEA (Data Envelopment Analysis), MARCOS (Measurements Alternatives and Ranking according to COmpromise Solution), and an optimization model. A DEA is a highly suitable procedure for evaluating the performance of multiple peer entities, often referred to as Decision-making Units (DMUs) or alternatives. On the other hand, the benefits of MARCOS are: (i) it considers both the ideal (ID) and anti-ideal (AID) scenarios and, (ii) it exemplifies the utility degree of each option in association to ID and AID. Lastly, the combination of cross-entropy and divergence measures effectively deal with the information loss occurred during the determining the weights of considered criteria. Therefore, the proposed hybrid model is more sensible and practical. According to the final results, Austria stands out as the top performer among the EU countries in implementing the SDGs and achieving favorable outcomes. ? 2024 Elsevier Ltd